Adolescent learner perceptions of foreign language assessment: Critical incident analysis - CZURA, ANNA (Glottodidactica, 2017)
This article reports on a study that aimed to explore adolescent learner perceptions of language assessment experiences and their beliefs about what makes a useful, valuable and highquality assessment. The data was collected by means of the critical incident technique (CIT) in which 25 lower secondary learners (aged 14–16) were asked to recall both positive and negative instances of assessment they had experienced in the course of their language education. The results reveal that the participants held generally positive views of language assessment and paid attention to such aspects of assessment as reliability, appreciation and authenticity. On the other hand, the importance of grades was prioritised over the learning value of assessment, which is characteristic of performance-oriented assessment environment.